2005
DOI: 10.1128/aac.49.6.2454-2459.2005
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic Structure of a Multiple-Drug-Resistant, Conjugative Plasmid from Campylobacter jejuni

Abstract: Partial sequence analysis of a tet(O) plasmid from a multiple-drug-resistant clinical isolate of Campylobacter jejuni revealed 10 genes or pseudogenes encoding different aminoglycoside inactivating enzymes, transposaselike genes, and multiple unknown genes from a variety of pathogenic and commensal bacteria. The plasmid could be mobilized by a P incompatibility group plasmid into Escherichia coli, where it apparently integrated into the chromosome and expressed high-level resistance to multiple aminoglycoside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
69
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 30 publications
4
69
0
Order By: Relevance
“…These contigs cover 37 kb of the 45.2 kb of pTet, and experimental analysis confirmed the presence of an approximately 45-kb plasmid in CG8486 (data not shown). The presence of a tetO gene on the CG8486 plasmid is consistent with the observed resistance of this strain to tetracycline and with the reported high incidence of tetracycline resistance among C. jejuni strains from Asia (26). The cpp2, cpp3, cpp4, cpp6, cpp7, cpp24, cpp25, and cmgB7 genes, which code for proteins with unknown functions, and repA, encoding a putative replication initiator protein, appear to be missing from the CG8486 plasmid, as sequenced.…”
Section: Vol 75 2007supporting
confidence: 56%
“…These contigs cover 37 kb of the 45.2 kb of pTet, and experimental analysis confirmed the presence of an approximately 45-kb plasmid in CG8486 (data not shown). The presence of a tetO gene on the CG8486 plasmid is consistent with the observed resistance of this strain to tetracycline and with the reported high incidence of tetracycline resistance among C. jejuni strains from Asia (26). The cpp2, cpp3, cpp4, cpp6, cpp7, cpp24, cpp25, and cmgB7 genes, which code for proteins with unknown functions, and repA, encoding a putative replication initiator protein, appear to be missing from the CG8486 plasmid, as sequenced.…”
Section: Vol 75 2007supporting
confidence: 56%
“…Thus, as shown in Table 5, homologs of other pTet and pCC31 genes (Cj8421_0812, Cj8421_0816, Cj8421_0820, and Cj8421_0821) are also found in zone 11. Additionally, there are two transposase genes (Cj8421_0822 and Cj8421_0823) at this locus that were found on a plasmid from another C. jejuni isolate from Thailand (40). This suggests that a transposition event was responsible for the integration of part of a tetracycline plasmid into the chromosome of CG8421.…”
Section: Composition Of Cpssmentioning
confidence: 95%
“…While multidrug resistance in C. jejuni isolates from poultry (9/104) is not common, the report of multidrug-resistant conjugative plasmids within C. jejuni (20) combined with the minimal regulation of antimicrobial usage (12) may result in the appearance of more such isolates.…”
mentioning
confidence: 99%
“…One study suggested that the tet(O) gene may be rapidly and spontaneously transferred in vivo without antimicrobial selection pressure between C. jejuni strains in the digestive tracts of chickens (3). Surveillance of tetracycline resistance is important due to the potential for plasmid-mediated transfer of the tet(O) gene (25) as well as genes encoding resistance to other antimicrobials (20) for other potential pathogens.…”
mentioning
confidence: 99%